Evaluasi Pemilihan Supplier Sayur Pada PT Dwi Tunggal Citra Catering Dengan Metode Analitycal Hierarchy Process (AHP) dan Best Worst Method (BWM) - Muhammad Raihan Zuchriadi Putra (Journal of Optimization System and Ergonomy Implementation, 2024)
PT Dwi Tunggal Citra Catering is a company focused on the catering industry that relies heavily on the effective and efficient selection of suppliers. This study implemented the Analytical Hierarchy Process (AHP) and Best Worst Method (BWM) methods. Based on the results of the study using the AHP method, the evaluation criterion weight value is 0.33, delivery is 0.29, flexibility is 0.19, responsiveness is 0.11 and cost is 0.08. The result of the processing of criteria data with the BWM method and processing the supplier's weight data with each of the criteria with AHP, shows that supplier with the highest optimal weight is supplier C with the optimal weight of 0.9, while supplier B occupies the second position with the optimum weight of 0.07, and supplier A has the optimal weight of 0. So it can be appreciated that the priority supplier to cooperate further on the process of vegetable procurement in PT Dwi Tunggal Citra Catering is supplier C.